Application of random regression model to estimate genetic parameters for average daily gains of Tunisian local kids population - Atoui A.; Carabaño M.J.; Díaz C.; Najari S. (Innovation for sustainability in sheep and goats, 2019)
A random regression model was applied to estimate co-variance components and genetic parameters for average daily gains (ADG1 from birth to 30 days, ADG2 from 30 to 60 days, ADG3 from 60 to 120 days, ADG4 from 120 to 150 days and ADG5 from 150 to 180 days). The data comprised13.095 records belonging to 945 local kids (progenies of 22 sires and 285dams) born between 1998 and 2014.The data were first assessed by SPSS Program in order to identify the fixed effects to be included in the model. Year*month, sex*type of birth, dam’s class weight were classified as fixed effects and dam’s age at kidding as covariate. Random effects included in model were direct additive genetic effect, maternal additive genetic effect, direct permanent environmental effect, maternal permanent environmental effect and residual effect. Direct and maternal heritability estimates of ADG ranged from 0.1 to 0.39 and 0.09 to 0.24, respectively, in which ADG1 had the lowest direct and highest maternal heritability estimates among the other age groups. Estimated co-variance components increased with age for direct effects. A significant maternal effect was found in the pre-weaning stage that decreased in the post-weaning stage. Unlike in breeds raised in favorable conditions, the estimated maternal component of variance was larger than the direct variance in the pre-weaning period, indicating the importance of maternal ability in this breed. A negative correlation was found between direct and maternal additive genetic traits. Estimates of genetic correlations among the traits studied were high and positive with values ranging from 0.06 to 0.98, whereas the magnitude of the phenotypic correlation ranged from 0.05 to 0.83. Heritability estimates indicate that selection for maternal and direct components of ADG is possible in this bred. However, direct components need to be evaluated after weaning for a more efficient selection.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)